Recruiting Expert Teachers into High-Needs Schools: Leadership, Money, and Colleagues - Amrein-Beardsley, Audrey (Education Policy Analysis Archives, 2012)
Teacher quality experts are urging policymakers to identify and target expert teachers and entice them to teach in high-needs schools. To understand what this might take, expert teachers in Arizona were surveyed to understand their job-related preferences to inform future recruitment policies. Findings should inform others about the important factors educational policymakers might consider when thinking about recruiting expert teachers into high-needs schools. These factors include the quality of the principal; salary, bonuses, and benefits; and the degree to which expert teachers can work in multiple roles to enhance student learning.